Assessing the Impact of Harassment by Peers: Incident Characteristics and Outcomes in a National Sample of Youth. (2nd January 2017) - Turner, Heather A.; Mitchell, Kimberly J.; Jones, Lisa; Shattuck, Anne
Abstract : Although there are widely held assumptions about the characteristics of peer bullying that are of greatest concern, very few studies have empirically assessed which characteristics most affect its impact. The current research addresses this gap by using a nationally representative U.S. sample of youth ages 10–20 to examine the relative effects of a variety of potentially aggravating incident characteristics on emotional, physical health, and school-related outcomes. Findings show support for power imbalance and duration (a stronger predictor than repetition) as incident characteristics that exacerbate the negative impact of peer harassment. However, several other incident characteristics have substantial effects with or without the presence of these qualities. Injury, sexual content, involvement of multiple perpetrators, and hate/bias components of peer harassment incidents each increased at least one negative outcome. Findings point to several features of peer harassment that can provide a basis for prioritizing victimization experiences in greatest need of intervention efforts.